Opportunistic infections associated with TNF-αα treatment. Issue 6 (December 2007) - Orenstein, Robert; Matteson, Eric L
The therapeutic agents known as TNF-αα inhibitors have been widely adopted as effective and standard therapy for many rheumatic diseases. Since their introduction into clinical practice, there has been concern that these agents that blunt host immunity to intracellular pathogens would lead to the development of opportunistic infections. Early reports of extrapulmonary tuberculosis, listeriosis, Pneumocystis jiroveci pneumonia and invasive fungal diseases seemed to confirm this association. Prospective and retrospective studies, registries, adverse reporting databases and experience from clinical practices indicate at least a twofold risk of serious bacterial infections with TNFs versus standard DMARDs but data are limited on opportunistic infections (OIs). This article will review the available data on OIs describing these risks and studies that have been done to reduce that risk.